Radios Get Smart. - Rubenstein, Roy (IEEE spectrum)
If radios could somehow use a portion of the broadcast TV spectrum without causing interference, cellular telephony and other important services would be able to exploit those bands. With more room to operate, cellphone calls would be a lot cheaper, as would mobile Internet access, which would get faster as well. Your handset would be able to pull in audio and visual entertainment from all over the globe, and videophoning would finally be a reality. To manage such feats, cellphone handsets would have to be able to shift their frequency of operation on demand and without packing in lots of extra hardware. Telecommunications engineers have a name for that goal software-defined radio. And the more visionary among them see it as a stepping-stone to an even more distant ideal. Their goal is a wireless device that is smart enough to analyze the radio environment and decide for itself the best spectral band and protocol to reach whatever base station it needs to communicate with, at the lowest level of power consumption. The name for such remarkable systems is "cognitive radios," and some are already emerging from the laboratory to be field-tested by the US military, which has long sponsored research in the area